THE OVERHEAD PROJECTOR–AND AID IN TEACHING ACCOUNTING. - Gordon, Dennis (The Accounting Review, 1962)
The overhead projector is a teaching aid that is ready and willing to work for accounting teachers today. Since the teacher operates the overhead projector, he faces the class at the front of the room. With a blackboard, the teacher not only turns his back on the class but spends much time writing and rewriting. Students can take notes when the overhead projector is in use because the room does not have to be darkened. Nevertheless, in order to make a more professional presentation, it is recommended that the front of the room should be darkened to about 80% of broad daylight. This will allow for deep color differentiation. The teacher can stand or sit while he is writing or placing transparencies on the machine. Instead of using the blackboard, the teacher can write on acetate sheets placed on the aperture or on a movable roll of acetate paper installed in the projector. Transparencies, prepared either commercially or with the aid of the school's visual aids department, enhance the use of the overhead projector. An imaginative teacher will find many new uses for the overhead projector in teaching accounting. Reproduction of business forms, documents, and legal instruments makes it possible to vividly show young students the underlying data for business transactions: a bond, stock certificate, promissory note, sales invoice, shipping report, or what-have-you.